El desarrollo del sistema anaeróbico a láctico como dirección determinante del rendimiento deportivo de las basquetbolistas categoría cadetes de federación deportiva de Chimborazo - Cando Brito, Karolina Janeth (2011)
In the present investigation parameters settled down for the training of the system anaerobic Aláctico, in the same one it is manifested more emphasis should be made in the system anaerobic Aláctico assisting the particularities of the basketball in what moment of the sportsman's preparation where most of their technical and tactical elements is carried out it in a strong, quick and explosive way, this investigation is since of traverse type the result it was evaluated in the basquetbolistas of Sport Federation of Chimborazo categories cadets, in the same way one observes by means of surveys and interviews to the trainers that more they pay attention to the work of the system Aerobic and not to the work of the system anaerobic Aláctico, most of trainers doesn't assume the importance that has the planning of the sport training and the conception of the decisive addresses and conditions of the sport training, for this reason it is recommended to consult the present work that leaves a theoretical base of the contemporary training in the basketball, it is recommended equally to carry out an analysis of the energy predominant system in each one of the sports to be able to guide, to plan and to evaluate the work co.